Enhancing community health system resilience: lessons learnt during the COVID-19 pandemic in Uganda through the qualitative inquiry of the COVID Task Force - Saito, Kiyoko; Komasawa, Makiko; Ssekitoleko, Robert; Aung, Myo Nyein (Frontiers in Public Health, 2023)
Objective This study aimed to explore the elements of a resilient community health system during the COVID-19 pandemic and discuss whether the frameworks described in previous studies can be applied to real-world situations with those who implemented the Community Engagement Strategy, a strategy to make health systems work in their communities during health crises in Uganda. Methods Focus group discussions (22 participants in total) were conducted with COVID Task Force members in four districts in Uganda in March 2022. These districts implemented a Community Engagement Strategy to ensure that health systems in their communities continued to function during health scares, and have been evaluated to ensure that the strategies have been implemented. Results A thematic analysis was applied. From the results some factors which can enhance the resiliency of community health systems were identified: including health “knowledge,” “communication,” “governance,” and “resources” health. The most important elements changed depending on the phase of the outbreak. VHTs are the key players in the transition from knowledge-and resource-oriented initiatives to communication and governance by community residents. Conclusion COVID-19, a new infectious disease, provides lessons for a resilient community health system. First, the health system should be flexible enough to be able to change the elements on which it is focused, and second, VHTs play an important role in the flexibility of the health system. This suggests that it is time to assess whether VHTs are still able to continue their activities after the pandemic is over, and whether the environment, including financial and non-financial support, has improved.